The Effect of Disclosure of Sustainability Report on Financial Distress with Company Performance as Intervening Variables - Dian Oktarina (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2018)
This study examines the effect of sustainability report disclosure on financial distress with corporate performance as an intervening variable. Corporate performance measured by Return on Assets (ROA). Sustainability report disclosure that used in this research were economic, environment, labor practices and decent work, human right, product responsibility, society. The population of this study is non-finance and banking companies listed at IDX. The sample of this research were 29 non-finance and banking companies listed in IDX during 2012-2016. This research used multiple linear regression and logistic regression method for testing the hypothesis. The results of this research showed that in the first model, sustainability report disclosure doesn't affect corporate performance. The second model showed that public responsibility aspect of sustainability report disclosure, negative effects on financial distress. The last model showed that corporate performance doesn't affect financial distress. Therefore, corporate performance can’t be used as an intervening variable. The implications of this study theoretically can provide evidence of the theory being tested related to the effect of sustainability report disclosure on financial distress with company performance as an intervening variable. Practically, this research is expected to be able to give an overview of the importance of sustainability reports disclosure to be made and published periodically by the company because this is considered to improve the performance of the company which will minimize or prevent companies from financial distress.